Tempo no trabalho: a experiência dos gerentes médios - Dantas, Alaíde Sipahi (2007)
The sociology of organizations is still made based on analytical schemas which are free of time (CLARK, 1985; HASSARD, 2000; GIDDENS, 2003). However, temporal concerns permeate every organization, what makes the concept of time extremely important to the organization studies. Based on this idea, this research had the ambition to approach the temporal dimension of work in the organizations; from the perspective of the individuals. Considering that the middle managers live a double tension inside organizations, which are originated from the top managers and the operational workers, we decided to investigate the way that the middle managers experience time at work. To review the temporal experience of the middle managers, twenty people, who work on organizations located at São Paulo, were interviewed and the content of the interviews analyzed. The content analyses methodology was used to analyze the material, which was colleted via semi-structured interviews. The interview analysis suggests that even though the time at work is, by the majority of professionals interviewed, defined as an economic resource, whose utilization must be maximally optimized, the temporal experience of the middle managers is not homogeneous. Environmental elements, common to all workers, tend to approximate the temporal experiences of middle managers. These elements, which are compression of time, sense of urgency, new technologies, characteristics related to the role of manager and organization or disorganization of workers and institutions, are associated to the economical and social scenario under which organizations function. However, personal characteristics, related to age, gender, personal values and experiences, besides the field in which the company functions also impact the way the middle managers experience time and deal with the temporal pressures. In conclusion, despite the fact that environmental elements are shared, with emphasis to the growing compression of time, the human nature and the impermanence of the social phenomenons reveal the complexity of the temporal experience of the middle managers at work. The homogeneity, objectivity and linearity represented by the clock, image of the time in the contemporary societies, is then confronted with the heterogeneous, subjective and cyclic aspects that are part of the temporal experience of the workers.